Politeness Strategies of Students in Communication By Whatsapps - Trisnawati, Winda (Universitas Muhammadiyah Muara Bungo, 2020)
This research was about politeness strategies of students in communication by whatsapp to lecturer. This research aimed to describe positive politeness strategies and negative politeness strategies that students used in communication by whatsapp. It was descriptive research design and qualitative and quantitative approach. The data of this research was whatsapp texts of English Department Students STKIP Muhammadiyah Muara Bungo. This research used purposive technique sampling. The The method of collecting data used observational method. The technique of collecting data used Non Participant Observation Technique (NPO), recording technique, and note taking technique. In analyzing data, the writer used referential method. For data presentation, the writer used informal method The researcher found Politeness strategy that students used in communication to the lecturer by whatsapp used two strategies. These are positive politeness strategy and negative politeness strategy. The biggest percentage of positive politeness strategy that students used was address form. It was 57.2%. The smallest percentage of positive politeness strategy that students used was joke. It was 0.1%. The biggest percentage of negative politeness strategy that students used was give deference. It was 30.2%. The smallest percentage of negative politeness strategy that students used was hedges on illocutionary force. It was 1.2%.